Pilot study suggests DNA methylation of the glucocorticoid receptor gene (NR3C1) is associated with MDMA-assisted therapy treatment response for severe PTSD - Lewis, Candace R.; Tafur, Joseph; Spencer, Sophie; Green, Joseph M.; Harrison, Charlotte; Kelmendi, Benjamin; Rabin, David M.; Yehuda, Rachel; Yazar-Klosinski, Berra; Cahn, Baruch Rael (Frontiers in Psychiatry, 2023)
Background Previous research has demonstrated that epigenetic changes in specific hypothalamic-pituitary-adrenal (HPA) genes may predict successful psychotherapy in post-traumatic stress disorder (PTSD). A recent Phase 3 clinical trial reported high efficacy of 3,4-methylenedioxymethamphetamine (MDMA)-assisted therapy for treating patients with severe PTSD compared to a therapy with placebo group (NCT03537014). This raises important questions regarding potential mechanisms of MDMA-assisted therapy. In the present study, we examined epigenetic changes in three key HPA axis genes before and after MDMA and placebo with therapy. As a pilot sub-study to the parent clinical trial, we assessed potential HPA epigenetic predictors for treatment response with genomic DNA derived from saliva (MDMA, n = 16; placebo, n = 7). Methylation levels at all 259 CpG sites annotated to three HPA genes (CRHR1, FKBP5, and NR3C1) were assessed in relation to treatment response as measured by the Clinician-Administered PTSD Scale (CAPS-5; Total Severity Score). Second, group (MDMA vs. placebo) differences in methylation change were assessed for sites that predicted treatment response. Results Methylation change across groups significantly predicted symptom reduction on 37 of 259 CpG sites tested, with two sites surviving false discovery rate (FDR) correction. Further, the MDMA-treatment group showed more methylation change compared to placebo on one site of the NR3C1 gene. Conclusion The findings of this study suggest that therapy-related PTSD symptom improvements may be related to DNA methylation changes in HPA genes and such changes may be greater in those receiving MDMA-assisted therapy. These findings can be used to generate hypothesis driven analyses for future studies with larger cohorts.